Agricultural valorization of composts produced by recycling organic waste - Slimani Rachid; Fatiha Metna Ali-Ahmed; Melissa Kanane; Arezki Hammoum (International Journal of Recycling of Organic Waste in Agriculture, 2023)
Purpose This paper investigates the composting recovery of different bio-wastes and the use of the composts produced as soil fertilizer and organic amendment.Method A composting process was carried out for 111 days using different organic wastes (fruits, vegetables, olive pomace, poultry, and cattle manure). The physicochemical properties of the generated compost were determined. The quality of the compost produced was evaluated by measuring pH, carbon/nitrogen (C/N), dry matter, and organic matter. A phytotoxicity test (germination test) was conducted to complete the analysis.Results The results of the physicochemical properties complied with AFNOR standards. The pH ranged between 7.3 and 8.7. The C/N ratio was between 10.05 and 18.46, and organic matter content varied between 33.6 and 72.7%. The phytotoxicity test showed that the safety of compost as a soil amendment is related to the applied dose and the type of crop.Conclusion The physicochemical parameters and phytotoxicity test showed that the compost obtained can be used as organic fertilizer due to its organic matter content and mineral elements.